MUSIC AS A REGULATORY TOOL FOR PEOPLE WITH AUTISM SPECTRUM DISORDER - Delfino, Alessandra de Fátima; Fagundes, Fabiana; Faria, Joice Bruna Santos; Spilla, Juliana Fernanda de Moraes; Chagas, Mariana Ap. Marques; Quintino, Máyra Patrícia Camargo; Julião, Pâmera Karina; de Oliveira, Roseli (Seven Editora, 2026)
This article aims to analyze the use of music as a tool for emotional and behavioral regulation in individuals with Autism Spectrum Disorder (ASD). Based on a literature review, it discusses how music can contribute to communication, social interaction, and self-regulation. Studies indicate that music therapy has positive effects on quality of life and symptom reduction in ASD, being a promising non-pharmacological intervention. It is concluded that music, when used intentionally, can support emotional expression, internal organization, and social bonding.